The presence of senescent peripheral T-cells is negatively correlated to COVID-19 vaccine-induced immunity in cancer patients under 70 years of age - Orillard, E.; Spehner, L.; Mansi, L.; Bouard, A.; Falcoz, A.; Lepiller, Q.; Renaude, E.; Pallandre, JR.; Vienot, A.; Kroemer, M.; Borg, C. (Frontiers in Immunology, 2023)
Purpose: Cancer patients are at risk of severe COVID-19 infection, and vaccination is recommended. Nevertheless, we observe a failure of COVID-19 vaccines in this vulnerable population. We hypothesize that senescent peripheral T-cells alter COVID-19 vaccine-induced immunity. Methods: We performed a monocentric prospective study and enrolled cancer patients and healthy donors before the COVID-19 vaccination. The primary objective was to assess the association of peripheral senescent T-cells (CD28-CD57+KLRG1+) with COVID-19 vaccine-induced immunity. Results: Eighty cancer patients have been included, with serological and specific T-cell responses evaluated before and at 3 months post-vaccination. Age ≥ 70 years was the principal clinical factor negatively influencing the serological (p=0.035) and specific SARS-CoV-2 T-cell responses (p=0.047). The presence of senescent T-cells was correlated to lower serological (p=0.049) and specific T-cell responses (p=0.009). Our results sustained the definition of a specific cut-off for senescence immune phenotype (SIP) (≥ 5% of CD4 and ≥ 39.5% of CD8 T-cells), which was correlated to a lower serological response induced by COVID-19 vaccination for CD4 and CD8 SIPhigh (p=0.039 and p=0.049 respectively). While CD4 SIP level had no impact on COVID-19 vaccine efficacy in elderly patients, our results unraveled a possible predictive role for CD4 SIPhigh T-cell levels in younger cancer patients. Conclusions: Elderly cancer patients have a poor serological response to vaccination; specific strategies are needed in this population. Also, the presence of a CD4 SIPhigh affects the serological response in younger patients and seems to be a potential predictive biomarker of no vaccinal response.